Peran Gembala Sebagai Upaya Pendidikan Agama Kristen Dalam Pembinaan Spiritualitas Remaja Pemuda - Widiyanto, Mikha Agus; Christin, Rina; Franclin, James (Vox Dei: Jurnal Teologi dan Pastoral, 2022)
Adolescent and youth as the next generation have important roles for the church. Their enthusiasm and creativity are very needed in participating for the church ministry and development. Adolescent and youth spirituality building through worship is being very fundamental so that they may involve in developing the church. Nevertheless, it cannot be dennied that adolescent and youth assume that activities outside the church is more interesting than worship, coachings through the worship is considered not suitable so that impact to their spiritual life. This study aimed to know pastor’s role as an effort of Christian Education to the adolescent and youth spirituality enhancement. This research was using survey method with causal on the analysis. The result showed that pastor has a significant role in Christian Education to the adolescent and youth spiritual improvement. Coaching conducted by the pastor through Christian Education teaching in worship or fellowship as well as joint activities will impact on adolescent and youth spiritual improvement to be more growing in Christ.